Towards a taxonomy of virtual work. (1st July 2013) - ,
Abstract : Whether they are used for real-money trading in massive multiplayer online role-playing games, on-line content production, working through crowdsourcing Internet marketplaces, modding, online gambling, playing human-based computation games, or just browsing, sharing files, and connecting with friends, online spaces have produced a wide range of new forms of activity. A growing number of scholars now refer to these as 'new labour activities', 'virtual work' or 'digital labour' or describe them as new sources of value creation for capital. Alongside these developments, new terms are emerging to describe the virtual workforce of which 'gold farmer', 'prosumer', 'Turker' or 'microworker' are only a few examples. Despite these new terms and categories, a coherent conceptual framework and understanding of what constitutes virtual work in more general terms is still lacking. No clear classification of this type of work yet exists, nor is there a clear distinction between it and the work that takes place in the 'real world'. This paper explores the obstacles that prevent the construction of such a classification and creating a clear definition and taxonomy of virtual work.